Dynamic quantification of the overall effect of dielectric polarization. (January 2023) - Shi, Jihong; Ao, Kelong; Firdous, Irum; Zhang, Xiangyang; Fahim, Muhammad; Wang, Lingyun; Daoud, Walid A.
Abstract: Due to the significance and universality of dielectric polarization, a quantitative assessment of this phenomenon is crucial for the sake of whether to avoid or exploit it. While triboelectrification and electrostatic induction have a direct relationship with dielectric polarization, there has been no prior work on bridging triboelectrification and dielectric polarization. To investigate the dielectric polarization effect, a dielectric-adjustable nanogenerator is built and the interplay of dielectric constant, electrical output, and surface charge is thoroughly investigated. After confirming the occurrence of self-polarization and polarization reversal during device operation, the surface charge accumulation and decay times are studied to understand the impact of dielectric polarization on prolonging the charge decay time and shortening the charge accumulation time, which are responsible for the device electrical output. Consequently, the feasibility of using the dynamic behavior of surface charge to quantify dielectric polarization is systematically studied. Graphical Abstract: ga1 Highlights: A dielectric adjustable nanogenerator is fabricated. Triboelectrification can induce self-polarization and polarization reversal. Surface charge variation is linked with dielectric polarization. A universal method for quantifying dielectric polarization is proposed.